2022
DOI: 10.1016/j.jceh.2021.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Perioperative Terlipressin Therapy for Preventing Acute Kidney Injury in Living Donor Liver Transplant Recipients: A Systematic Review and Meta-Analysis

Abstract: Background: Acute kidney injury (AKI) is common in the perioperative transplant period and is associated with poor outcomes. Few studies reported a reduction in AKI incidence with terlipressin therapy by counteracting the hemodynamic alterations occurring during liver transplantation. However, the effect of terlipressin on posttransplant outcomes has not been systematically reviewed. Methods: A comprehensive search of electronic databases was performed. Studies reporting the use of terlipressin in the perioper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A total of 4271 citations were retrieved and screened after duplicate removal, including 4 meta-analyses used for supplemental screening (Supplemental Material Section 1 and Figure S1, SDC, http://links.lww.com/TP/C835). [45][46][47][48] We included 25 RCTs (Figure S1, SDC, http://links.lww. com/TP/C835; Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 4271 citations were retrieved and screened after duplicate removal, including 4 meta-analyses used for supplemental screening (Supplemental Material Section 1 and Figure S1, SDC, http://links.lww.com/TP/C835). [45][46][47][48] We included 25 RCTs (Figure S1, SDC, http://links.lww. com/TP/C835; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4271 citations were retrieved and screened after duplicate removal, including 4 meta-analyses used for supplemental screening ( Supplemental Material Section 1 and Figure S1, SDC , http://links.lww.com/TP/C835). 45-48 We included 25 RCTs ( Figure S1, SDC , http://links.lww.com/TP/C835; Table 1). 49-73 Detailed interventions and main cointerventions used in individual studies (fluid management and coagulation management protocols) are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1,38) During the treatment, the resolution of AKI has a good prognosis (38-40%), and the progression of AKI has a mortality rate of approximately 75%. (38)(39)(40)(41) Biomarkers like NGAL, KIM-1, and IL-18 can be of some help in predicting renal failure and the development of ATN. (38)(39)(40)(41)(42)…”
Section: Renal Failurementioning
confidence: 99%
“…(38)(39)(40)(41) Biomarkers like NGAL, KIM-1, and IL-18 can be of some help in predicting renal failure and the development of ATN. (38)(39)(40)(41)(42)…”
Section: Renal Failurementioning
confidence: 99%